1999
DOI: 10.1016/s0954-6111(99)90010-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of blood cultures in community-acquired pneumonia requiring hospitalization: influence of antibiotic treatment before admission

Abstract: It has been previously shown that antibiotics given before hospitalization significantly reduce the proportion of positive blood cultures in community-acquired pneumonia (CAP). The aim of this prospective study was to compare the utility and cost-benefits of blood cultures in patients, hospitalized for moderate CAP, who had or had not received antibiotic therapy prior to admission. During 1 year, 53 patients were included and separated into two groups: group 1 patients had not received antibiotic treatment pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 20 publications
4
43
1
3
Order By: Relevance
“…The diagnostic performance of SF was significantly superior to BC in patients under antibiotic treatment. As expected (6,17), the results of BC were affected by the antibiotic pretreatment, a very common situation in febrile patients admitted to an internal medicine ward. Indeed, in our population, 49% of the patients had been receiving antibiotics for Ն24 h before sampling.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The diagnostic performance of SF was significantly superior to BC in patients under antibiotic treatment. As expected (6,17), the results of BC were affected by the antibiotic pretreatment, a very common situation in febrile patients admitted to an internal medicine ward. Indeed, in our population, 49% of the patients had been receiving antibiotics for Ն24 h before sampling.…”
Section: Discussionsupporting
confidence: 63%
“…The diagnosis of sepsis relies heavily on blood culture (BC), which detects circulating living bacteria or fungi and tests susceptibility to antimicrobials. However, the sensitivity of BC is limited, particularly when antibiotics have already been administered (6,17), and may not provide time-critical results that can impact on early management (2). Indeed, culturing, identification, and drug-susceptibility testing may require more than 48 h (7).…”
mentioning
confidence: 99%
“…3A). This could be due to a drastic decrease in the sensitivity of blood culture after antibiotic therapy (17,19,31). To investigate the relationship of mecA DNA levels to blood culture positivity and antibiotic usage, we analyzed the mecA DNA levels in blood culture-positive and -negative samples subgrouped by the duration of anti-MRSA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of S. aureus-related infections, it was reported that positive blood cultures during follow-up and the persistence of fever were suggestive of a complicated course (6,15,37). However, the drastic decrease in the sensitivity of blood culture after the initiation of antimicrobial therapy, even when special culture media are used, has made the use of blood cultures to monitor responses to therapy and outcomes very difficult (17,19,31,36). On the other hand, most of the realtime PCR assays used for the detection of MRSA have been qualitative in nature and have used specimens from blood culture bottles or nasal swabs rather than blood samples directly and therefore have provided little information regarding the MRSA load in blood (16,20,24,43,48).…”
mentioning
confidence: 99%
“…72 Moreover, this test, including antimicrobial susceptibility, requires .72 hours for bacteria, and .60 hours for fungi, 69 and BCs are always collected before initiating antibiotic therapy in order to increase the sensitivity. 73 In spite of these limitations, a positive BC remains an important diagnostic clue or a confirmation for the physicians. The optimal assay result depends on volume of sample, moment of sampling, and accuracy with which this is carried out.…”
Section: Molecular Techniques For Assay Of Sepsis In Positive Bcsmentioning
confidence: 99%